A new species of Kaloula (Amphibia: Anura: Microhylidae) from southern Guangxi, China - Mo, Yunming; Zhang, Wei; Zhou, Shichu; Chen, Tianbo; Tang, Huaxing; Meng, Yuanjun; Chen, Weicai (Zootaxa, 2013)
A new species of narrow-mouthed frog of Kaloula is described in the Nonggang National Nature Reserve, Sino-Vietnamese border region of southern China. Kaloula nonggangensis sp. nov. is distinguished from its congeners by a combination of the following characters: medium size (SVL 41.4–52.7 mm in 18 adult males, 52.2 mm in 1 female); smooth or slightly rough olive dorsum with irregular dark-green marks and brown spots; tips of the fingers widely dilated and truncated; males with nearly fully webbed toes; males with two side protuberant osseous tubercles on the upper surface of the tips of fingers and chest beige with small lemon-colored spots. K. nonggangensis sp. nov. is found in habitats ranging from cultivated fields adjacent to the forest to primary evergreen forest in karst habitats. Based upon a 16S ribosomal RNA mitochondrial gene fragment, K. nonggangensis sp. nov. is embedded within the K. verrucosa group (including K. borealis, K. rugifera and K. verrucosa), and displays a low genetic distance to these species (< 3%). Considering the distinct morphology and karyotype we nevertheless suggest a status as separate species for these allopatrically distributed lineages.